Spory o powieść w dyskusjach krytycznoliterackich drugiej emigracji niepodległościowej - Pasterska, Jolanta (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2021)
The polemic presented in the work concerns the clash of swords over the concept of the novel led by Second Migration Over Independence circles and had two main aspects. First, in the context of so-called literary engagement and resulted directly from the goals of Polish Migration and the associated conceptual and moral aspects. The other aspect of the conflict was more universal in nature and was tied to discussion of the novel per se – its greatest possible ‘largeness’ for it to answer the challenges set by a postwar world amidst ruin. In the context of this worldview there occurs both a longing for the Polish migration ‘masterpiece’ (Epopee in Exile) and the polemic around the form of the novel. The discussion of standpoints is set against a historical-literary outline examined from three main perspectives: generational, aesthetic and that of worldview.
Literary Polemics On the Novel – Second Migration Over Independence